2020
DOI: 10.3390/pr8040439
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Fluid Flow and In-Cylinder Air Flow Characteristics for Higher Viscosity Fuel Applications

Abstract: Generally, the compression ignition (CI) engine that runs with emulsified biofuel (EB) or higher viscosity fuel experiences inferior performance and a higher emission compared to petro diesel engines. The modification is necessary to standard engine level in order to realize its application. This paper proposes a guide vane design (GVD), which needs to be installed in the intake manifold, is incorporated with shallow depth re-entrance combustion chamber (SCC) pistons. This will organize and develop proper in-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In order to enhance the turbulence intensity, the vortex flow needs to be increased [39]. Nevertheless, the flow structure changes dramatically along the cylinder (due to change in geometry at the intake stroke) influenced by the engine geometry as reported by Hamid et al [40,41]. Thus, as is clearly seen in Figure 11, a progressive airflow was achieved and demonstrated via the installation of the 0.60R GVD design.…”
Section: Swirl Tumble and Cross Tumble Ratio (R S R T And R Ct )mentioning
confidence: 85%
“…In order to enhance the turbulence intensity, the vortex flow needs to be increased [39]. Nevertheless, the flow structure changes dramatically along the cylinder (due to change in geometry at the intake stroke) influenced by the engine geometry as reported by Hamid et al [40,41]. Thus, as is clearly seen in Figure 11, a progressive airflow was achieved and demonstrated via the installation of the 0.60R GVD design.…”
Section: Swirl Tumble and Cross Tumble Ratio (R S R T And R Ct )mentioning
confidence: 85%
“…Fluid shear stresses and wall friction degrades the swirl and tumble kinetic energies [22]. The resulting shear torques τ z,shr and τ x,shr can be determined by integrating the wall friction over the chamber surface and fluid stress over the chamber volume but would require knowledge of the spatial flow field.…”
Section: Evolutions Mech Engmentioning
confidence: 99%
“…Nevertheless, R CT has a close correlation with R s and R T . Bari et al found that in order to improve R CT in a CI engine, R s and R T values need to be improved [41,42]. Prasad et al reported that enhancing the R CT air motion is a crucial issue, as it has an impact on increasing the air-fuel mixing process, achieving faster burning rates, increasing indicated efficiency, and improving the air management [43].…”
Section: In-cylinder Swirl (R S ) Tumble (R T ) and Cross Tumble Ratio (R Ct )mentioning
confidence: 99%